2019
DOI: 10.1108/apjml-06-2019-0411
|View full text |Cite
|
Sign up to set email alerts
|

User willingness to purchase applications on mobile intelligent devices: evidence from app store

Abstract: Purpose The purpose of this paper is to explore the facilitating and inhibitory factors on paid app downloading intentions based on an integrated valence theory, considering two social environmental factors and two intermediate variables: perceived value and perceived trust. Design/methodology/approach This study is based on the integrated valence theory. After collecting users’ data, partial least square analysis is used to examine the main driving and constraining factors for users to download paid apps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 78 publications
3
29
0
13
Order By: Relevance
“…Similar to previous research on mobile Apps [38], App enjoyment is found to be another important factor that influences purchasing intentions. Furthermore, a previous study [11,81] supports the importance of perceived enjoyment with regard to behavioral intentions to download mobile Apps. Enjoyment has a positive relationship with consumers' purchasing intentions.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Similar to previous research on mobile Apps [38], App enjoyment is found to be another important factor that influences purchasing intentions. Furthermore, a previous study [11,81] supports the importance of perceived enjoyment with regard to behavioral intentions to download mobile Apps. Enjoyment has a positive relationship with consumers' purchasing intentions.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, hedonic value has been recognized as one of the key antecedents that significantly influences how consumers make their purchasing decisions [34]. It has been argued by Tang et al [11] that "App consumers focus more on satisfying their own inner spiritual needs rather than targeting practical purpose" (p. 1632). Further, enjoyment positively influences mobile App usage intentions because, when consumers' entertainment requirements are met, the pleasurable feelings about the App are realized.…”
Section: Research Model and Its Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the value-in-use components should not represent knock-out criteria for the first use. Research has shown that privacy concerns have a negative influence on a customer's intention to download a mobile app (Tang et al 2019;Klumpe et al 2018;Wottrich et al 2018;Gu et al 2017), which is why we assume that privacy concerns are such a knock-out criterion of use. Therefore, we conclude that privacy concerns are not a component of value-in-use, but rather an upstream construct that affects the customer's initial decision to use the app for the first time.…”
Section: Conceptualization Of Mobile Location-based Services' Value-imentioning
confidence: 99%